Nanoscience and plant-soil systems - Ghorbanpour, Mansour; Manika, Khanuja; Varma, A. 1939- (Springer, 2017)
This book provides in-depth reviews of the effects of nanoparticles on the soil environment, their interactions with plants and also their potential applications as nanofertilizers and pesticides. It offers insights into the current trends and future prospects of nanotechnology, including the benefits and risks and the impact on agriculture and soil ecosystems. Individual chapters explore topics such as nanoparticle biosynthesis, engineered nanomaterials, the use of nanoclays for remediation of polluted sites, nanomaterials in water desalination, their effect on seed germination, plant growth, and nutrient transformations in soil, as well as the use of earthworms as bioremediating agents for nanoparticles. It is a valuable resource for researchers in academia and industry working in the field of agriculture, crop protection, plant sciences, applied microbiology, soil biology and environmental sciences.- Resumé vydavatel
Keywords: nanočástice; půdní mikrobiologie; nanotechnologie; rostliny; nanoparticles; soil microbiology; nanotechnology; plants; elektronické knihy; sborníky; electronic books; papers of several authors